Positive correlational shift between crevicular antimicrobial peptide LL-37, pain and periodontal status following non-surgical periodontal therapy. A pilot study - David Madruga; Miguel M Garcia; Luca Martino; Haidar Hassan; Ghada Elayat; Lucy Ghali; Laura Ceballos (BMC, 2023)
Abstract Background Periodontitis has a high prevalence and uncertain recurrence. Unlike the pro-inflammatory cytokine profile, little is known about the anti-inflammatory cytokine and antimicrobial peptide overview following treatment. The present study aimed to evaluate if any of the antimicrobial peptide LL-37, interleukin (IL) 4, 10 and 6 together with the volume of gingival crevicular fluid (GCF) and total protein concentration in GCF could be used as correlative biomarkers for the severity in periodontitis as well as prognostic factors in the management of the disease. Methods Forty-five participants were recruited and allocated to the healthy (15), Stage I-II (15) or Stage III-IV periodontitis (15) group. Along with periodontal examination, GCF samples were obtained at baseline and 4-6 weeks following scaling and root planing (SRP) for the periodontitis groups. GCF samples were analyzed by ELISA kits to quantify LL-37 and IL-4, -6 and − 10. One-way ANOVA followed by Dunnett's test was used to determine differences among the three groups at baseline. Two-way ANOVA followed by Sidak's post-hoc test was used to compare between pre- and post-SRP in the two periodontitis groups. Results The amount of GCF volume was significantly correlated to the severity of periodontitis and decreased following SRP, particularly in the Stage III-IV group (p < 0.01). The levels of LL-37, IL-6, and pain and periodontal clinical parameters were significantly correlated to the severity of periodontitis. IL-4 and IL-10 in the periodontitis groups were significantly lower than the healthy group (p < 0.0001) and barely improved following SRP up to the level of the healthy group. Conclusions With the limitations of this study, crevicular LL-37 may be a candidate for a biomarker of periodontitis and the associated pain upon probing. Trial registration The study was registered in clinical trials.gov, with number NCT04404335, dated 27/05/2020.